A probabilistic analysis of border nodebased MFR routing protocol for vehicular ad hoc networks. (2015) - Raw, Ram Shringar; Lobiyal, Daya K.; Das, Sanjoy
In this paper, we examined the significance of positionbased routing with bordernodebased forwarding for vehicular ad hoc network (VANET) to optimise path length between vehicles. We have mathematically evaluated the performance of border nodebased forwarding method such as Border nodebased MFR (BMFR). BMFR strongly avoids the interior nodes within the transmission range for further transmitting the packets. Furthermore, we have developed a mathematical model for BMFR to determine average number of hop counts, expected distance between source and destination, and maximum progress of the nexthop node towards the destination node using Poisson distribution for node deployment. Analytical and simulation results indicate that BMFR can provide efficient routing in VANETs. In our work, results clearly show that using the bordernodes is an advantage to maximise the performance of routing protocol in terms of average number of hops with minimum delay. We have mathematically simulated the proposed protocol in MATLAB and compared the result with existing routing protocol MFR.